Pengaruh Capital Structure, Firm Performance Dan Good Corporate Governance Terhadap Earnings Management - Feliciana Stephanie Suryata, Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This research was conducted to analyze the effect of capital structure, firm performance and good corporate governance to earnings management on industry companies listed in Indonesia Stock Exchange period 2017-2019. The technique used in this research for determining the research sample was purposive sampling. The number of research sample is 75 companies from 182 companies registered as industry companies. This research was using quantitative approach. Data analysis method used in this research is multiple linear regression analysis. The result showed that in simultaneously capital structure, firm performance and good corporate governance has a significant effect on earnings management. Meanwhile, the result of partial research shows that capital structure and firm performance has a positive and significant effect on earnings management. Board size has a negative and insignificant effect on earnings management. Board independence and audit committee has a positive and insignificant effect on earnings management.